A clearer picture of change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A climate expert from the UK discusses how improved understanding and information about changing weather patterns in Africa should improve the response of governments and people.